Treatment of osteomyelitis using local bio degradable antibiotic pellets - Mohd Yusof, Nazri (AO Research Institute Davos, 2019)
INTRODUCTION: Local antibiotic pellet using bio degradable ceramic such as calcium sulphate and calcium phosphate has been proven to be as effective as bone cement antibiotic beads in the treatment of osteomyelitis. It’s obliterate dead space and provide high concentration of local antibiotic with low systemic level thus reducing the side effect to the kidney. The main advantage of bio degradable ceramic is that it does not require second surgery for removal and its antibiotic release is more complete than the bone cement. The aim of this study is to investigate the clinical outcome of patients treated with bio degradable antibiotic pellets following debridement of osteomyelitis foci.